Coulomb interactions in single charged self-assembled quantum dots: Radiative lifetime and recombination energy - Dalgarno, P; Smith, J; McFarlane, J; Gerardot, B; Karrai, K; Badolato, A; Petroff, P; Warburton, R (2008)
We present results on the charge dependence of the radiative recombination lifetime, τ, and the emission energy of excitons confined to single self-assembled InGaAs quantum dots. There are significant dot-to-dot fluctuations in the lifetimes for a particular emission energy. To reach general conclusions, we present the statistical behavior by analyzing data recorded on a large number of individual quantum dots. Exciton charge is controlled with extremely high fidelity through an n -type field effect structure, which provides access to the neutral exciton (X0), the biexciton (2 X0), and the positively (X1+) and negatively (X1-) charged excitons. We find significant differences in the recombination lifetime of each exciton such that, on average, τ (X1-) /τ (X0) =1.25, τ (X1+) /τ (X0) =1.58, and τ (2 X0) /τ (X0) =0.65. We attribute the change in lifetime to significant changes in the single particle hole wave function on charging the dot, an effect more pronounced on charging X0 with a single hole than with a single electron. We verify this interpretation by recasting the experimental data on exciton energies in terms of Coulomb energies. We directly show that the electron-hole Coulomb energy is charge dependent, reducing in value by 5%-10% in the presence of an additional electron, and that the electron-electron and hole-hole Coulomb energies are almost equal. © 2008 The American Physical Society.